Healthcare Information Systems (HIS): Implementation Challenges in Developing Countries (Bangladesh Journal of Medical Science, 2024)
In developing nations, the establishment of sustainable healthcare information systems (HIS) is often hindered by insufficient government policies and outdated technology. Bangladesh is a notable example where many patients lack proper healthcare access due to fragmented and non-digitally recorded data. Research has shown that standardized hospital healthcare systems can streamline patient management, increasing the capacity to serve more patients simultaneously. These systems have the potential to improve healthcare in developing nations significantly. This article offers an overview of the key obstacles that impede HIS implementation in these countries. The study looked at relevant information systems literature using a systematic literature review (SLR). The systematic literature review (SLR) was governed by a review process, and relevant studies were gathered from three databases: IEEE Xplore, EBSCO Databases, and ScienceDirect. A total of 4014 papers were initially found. However, only 11 main studies were included for analysis after a careful selection procedure governed by inclusion and exclusion criteria. This study found 24 obstacles to adopting Healthcare Information Systems (HIS) in developing countries, divided into six groups. These obstacles include a lack of financial assistance, inadequate infrastructure, inadequate education and awareness, cultural and political obstacles, reluctance to change, and poor system quality.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 314-326